G106 Providing Neonatal resuscitation at the maternal bedside with an intact umbilical cord. (7th April 2014) - Thomas, MR; Yoxall, CW; Weeks, AD; Duley, L
Abstract : Aims: Deferring cord clamping at very preterm births may be beneficial for babies. However, deferring cord clamping should not mean that newborn resuscitation is deferred. Providing initial care at birth at the mother's bedside would allow parents to be present during resuscitation, and would potentially allow initial care to be given with the cord intact. Allowing parents to be present during neonatal resuscitation may be of benefit to them, as in other areas of resuscitation medicine. The aim of this study was to evaluate the usability, acceptability and safety of a new mobile trolley for providing newborn resuscitation, and to assess whether it allows initial care with the umbilical cord intact. Methods: The trolley was used when a clinician trained in newborn life support was required. Clinicians were asked to complete a questionnaire about their experience of using the trolley. Serious adverse events were reported. 78 babies were managed on the trolley. Median (range) gestation was 34 weeks (24 to 41 weeks). Median (range) birth weight was 2470 grams (520 to 4080 grams). The full range of resuscitation procedures has been successfully provided including intubation and surfactant administration on 20 occasions. Only one baby has required emergency umbilical venous catheterisation. In most situations, the baby could be resuscitated with umbilical cord intact, although on 18 occasions the cord was too short to reach the trolley. 77/78 babies had a post resuscitation temperature above 36°C. There were no adverse events. Most clinicians rated the trolley as 'the same', 'better' or 'much better' than conventional resuscitation equipment. 69% of clinicians felt that the overall experience for parents was better. Informal feedback from parents has been positive. Conclusions: Immediate stabilisation at birth and resuscitation can to be performed successfully and safely at the bedside using this trolley. In most cases this could be achieved with an intact umbilical cord. This appears to be acceptable to both clinicians and parents although further detailed qualitative assessment is required.